Survival of Cervical Cancer Patients Undergoing Neoadjuvant Chemotherapy (NACT) and Radical Hysterectomy at Dr. Saiful Anwar General Hospital Malang - Yahya Irwanto; Rizki Wahyuni (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2026)
Introduction: Cervical cancer remains a significant health burden, particularly in developing countries where access to radiotherapy is limited. Neoadjuvant chemotherapy (NACT) followed by radical hysterectomy has emerged as an alternative treatment strategy for locally advanced cervical cancer. This study aims to evaluate the survival outcomes and histopathological characteristics of patients with stage IIB cervical cancer who underwent NACT followed by radical hysterectomy in Dr. Saiful Anwar General Hospital. Material and Methods: This retrospective study analyzed medical records of patients with stage IIB cervical cancer who received NACT followed by radical hysterectomy at Dr. Saiful Anwar General Hospital from January 2021 to July 2022. Patients with incomplete medical records or loss to follow-up were excluded. Data analysis included descriptive survival outcomes and histopathological findings. Associations between histopathological variables and mortality were analyzed using Fisher’s exact. A p-value ≤0.05 was considered significant. Results: A total of 51 patients met the inclusion criteria. During the follow-up period, 39 patients (76.5%) were alive, while 12 patients (23.5%) had died. The estimated overall survival probability at 24 months was 76.5% (95% CI: 65.7–89.0). Fisher’s exact test demonstrated no statistically significant association between histopathological subtype and mortality (p = 0.069). No statistically significant association was observed between histopathological subtype and mortality. Conclusion: Survival outcomes of stage IIB cervical cancer treated with neoadjuvant chemotherapy followed by radical hysterectomy in a tertiary setting. Histopathological subtype and absence of residual tumor were associated with improved survival. Further comparative studies are required to evaluate the effectiveness relative to standard treatments.